REMOVAL OF EXTERNALITIES IN TOURISM BY MEANS OF TOUR OPERATOR SPECIALISATION AND EDUCATION - Jasmina Grižnić (Economic Review, 2018)
In analysis of specialisation in tourism it is important to reflect on several related terms which have become apparent with the emergence of modern times. This concerns competitiveness, positioning in the tourism market, education and innovativeness. Specifically, it is believed that all the listed terms are closely linked to the process of specialisation in tourism and, more accurately, that the said process affects them or, within a specific context, that it becomes determined by them. At the international level, the most important and most active market is the European market; more precisely, the European Union market, that is to say, its emissive and receptive character. For some time, the leading destinations have stressed the importance of specialisation in tourism, especially the green ones. Wishing to retain their market position, tour operators can help destination sustainable development by specialisation. Due to a large stakeholder network in destinations, former “big players” know them well and propose new tourist attractions. By the research, specialisation in tourism is analysed, as well as the levels and roles of specialisation in the removal of externalities. At the same time, the paper represents a contribution to the analysis of internal and external risks, as it points to the importance of their removal on the example of specialisation in Croatian tourism. While the majority of stakeholders in tourism are oriented towards the profit and creation of additional income in tourism, realistic circumstances and possibilities for development of destination tourism can be realised also through benefits of the forms of selective tourism.